2021
DOI: 10.3390/pathogens10020206
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Genotyping of Giardia duodenalis in Mostly Asymptomatic Indigenous People from the Tapirapé Tribe, Brazilian Amazon

Abstract: Little information is available on the occurrence and genetic variability of the diarrhoea-causing enteric protozoan parasite Giardia duodenalis in indigenous communities in Brazil. This cross-sectional epidemiological survey describes the frequency, genotypes, and risk associations for this pathogen in Tapirapé people (Brazilian Amazon) at four sampling campaigns during 2008–2009. Microscopy was used as a screening test, and molecular (PCR and Sanger sequencing) assays targeting the small subunit ribosomal RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 104 publications
(76 reference statements)
2
12
0
Order By: Relevance
“…(9) A similar scenario occurred among indigenous peoples in Mato Grosso, Midwest Brazil, where assemblage B was also predominant. (10) Globally, most studies showed a higher prevalence of assemblage B (20) with the exception of Australia, where A was predominant. (4) The diversity of sub-assemblages identify here, was also been demonstrate in other studies.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…(9) A similar scenario occurred among indigenous peoples in Mato Grosso, Midwest Brazil, where assemblage B was also predominant. (10) Globally, most studies showed a higher prevalence of assemblage B (20) with the exception of Australia, where A was predominant. (4) The diversity of sub-assemblages identify here, was also been demonstrate in other studies.…”
Section: Discussionmentioning
confidence: 98%
“…(8,16) Considering only larger population studies, assemblage A was most frequently identified in Southeastern Brazil, (6,17,18) but assemblage B has been identified as prevalent in other Brazilian regions. (10,19) Interestingly, in the only genotyping study of G. duodenalis in Amazonas/Brazil, conducted in Santa Izabel do Rio Negro, an area inhabited mainly by indigenous peoples, assemblage B was predominant. (9) A similar scenario occurred among indigenous peoples in Mato Grosso, Midwest Brazil, where assemblage B was also predominant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations